Communication Style of @halodoc.id Content on the Tiktok Platform Regarding Hair Health Awareness - M. Zidan Arifaini; Farida Nurul Rakhmawati (International Journal of Psychology and Mental Health, 2025)
This research examines the communication style employed by @halodoc.id on the TikTok platform specifically regarding hair health education content. The study analyzes how this healthcare information provider adapts medical knowledge into accessible, engaging short-form videos while maintaining accuracy. Through content analysis of @halodoc.id's hair health-related videos, the research identifies key communication strategies including the use of visual demonstrations, simplified medical terminology, expert testimonials, and interactive elements that encourage viewer engagement. The findings suggest that @halodoc.id effectively balances educational substance with entertainment value, employing a conversational tone and culturally relevant examples to enhance audience comprehension and retention of hair health information. This approach has implications for health communication in digital spaces, demonstrating how medical content can be successfully adapted for social media platforms without compromising informational integrity.